2013
DOI: 10.4161/idp.24684
|View full text |Cite
|
Sign up to set email alerts
|

The alphabet of intrinsic disorder

Abstract: The ability of a protein to fold into unique functional state or to stay intrinsically disordered is encoded in its amino acid sequence. Both ordered and intrinsically disordered proteins (IDPs) are natural polypeptides that use the same arsenal of 20 proteinogenic amino acid residues as their major building blocks. The exceptional structural plasticity of IDPs, their capability to exist as heterogeneous structural ensembles and their wide array of important disorder-based biological functions that complements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 247 publications
(412 reference statements)
2
55
0
Order By: Relevance
“…KEIF was predicted to belong to the R1 region of the Das-Pappu plot [33,34] in Figure 2b, which predicted that KEIF assumes a globular structure in aqueous solution. Figure 2c shows the disorder propensity per amino acid based on fractional difference (C DisProt − C PDB )/C PDB as described by Uversky (2013) [35]. Overall, the sequence did not seem to contain a substantial amount of disorder-promoting residues, although a cluster of disorder-promoting residues was found closer to the C-terminal end of the sequence (residues Pro-24-Gln-28), suggesting that this part of the peptide has higher propensity for disordered conformations.…”
Section: Charge-distribution Isoelectric-point and Das-pappu Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…KEIF was predicted to belong to the R1 region of the Das-Pappu plot [33,34] in Figure 2b, which predicted that KEIF assumes a globular structure in aqueous solution. Figure 2c shows the disorder propensity per amino acid based on fractional difference (C DisProt − C PDB )/C PDB as described by Uversky (2013) [35]. Overall, the sequence did not seem to contain a substantial amount of disorder-promoting residues, although a cluster of disorder-promoting residues was found closer to the C-terminal end of the sequence (residues Pro-24-Gln-28), suggesting that this part of the peptide has higher propensity for disordered conformations.…”
Section: Charge-distribution Isoelectric-point and Das-pappu Analysismentioning
confidence: 99%
“…KEIF location is indicated by white circle in Region R1. (c) Disorder propensity per amino acid (C DisProt − C PDB )/C PDB , as described byUversky (2013) [35]. (d) Probability prediction of disordered regions and disordered binding regions using PrDOS (green)[36], IUPred2A (light purple), and ANCHOR2 (dark purple) algorithms[37].…”
mentioning
confidence: 99%
“…Prior work showed that this Gcn4 derivative has no inherent AD function and that it can accept a wide variety of natural and synthetic ADs, permitting activation of yeast Gcn4-dependent genes Warfield et al, 2014). By varying the ratio of the four DNA bases separately at codon positions 1, 2, and 3 (Labean and Kauffman, 1993), we made two libraries that either (1) biased the randomized coding sequences for residues normally enriched in IDRs (Uversky, 2014) or (2) that encoded an approximately equal representation of all amino acids.…”
Section: A High-throughput Screen For Synthetic Activation Domainsmentioning
confidence: 99%
“…[1][2][3][4] IDPs are represented by a collection of a dynamically inter-converting population of structures, termed an 'ensemble of conformations.' In addition to proteins that are fully disordered, many proteins have significant disordered portions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to proteins that are fully disordered, many proteins have significant disordered portions. [1][2][3][4] IDPs are represented by a collection of a dynamically inter-converting population of structures, termed an 'ensemble of conformations.' The free energy required to transition between conformational states within the ensemble does not differ greatly between the various conformations.…”
Section: Introductionmentioning
confidence: 99%